Downregulation of Aquaporin 9 Exacerbates Beta-amyloid-induced Neurotoxicity in Alzheimer's Disease Models In vitro and In vivo. (1st December 2018) - Liu, Jing-Yi; Chen, Xiao-Xin; Chen, Hai-Yong; Shi, Jun; Leung, George Pak-Heng; Tang, Sydney Chi-Wai; Lao, Li-Xing; Yip, Henry Ka-Fun; Lee, Kai-Fai; Sze, Stephen Cho-Wing; Zhang, Zhang-Jin; Zhang, Kalin Yanbo
Graphical abstract: Highlights: Age-related decrease in BDNF and increase in APP expression occurred in the brain of APPswe/PS1dE9 (Tg) mice. Decrease in AQP9 expression was associated with decreased BDNF and increased APP expression in the brain of Tg mice. Decrease in AQP9 expression was related to increased apoptosis in the brain of Tg mice. Aβ1–40 induced apoptosis in PC12 cells while down-regulating the expression of AQP9. AQP9 knockdown enhanced Aβ1–40 -induced toxicity and apoptosis in PC12 cells. Abstract: Alzheimer's disease (AD) is the most common cause of dementia in the elderly, characterized by progressive cognitive dysfunction. Aquaporin 9 (AQP9) is an aquaglyceroporin membrane channel shown biophysically to conduct water, glycerol, and other small solutes. In our study, we reported for the first time an age-associated decrease in AQP9 mRNA and protein expressions in both hippocampus and cerebral cortex of APPswe/PS1dE9 (Tg) AD mice at 3, 6 and 10 months of age. Consistently, we observed a dose-dependent downregulation of AQP9 expression in PC12 cells after treatment with amyloid-beta protein 1–40 (Aβ1–40 ). Pre-treatment with AQP9 small interfering RNA led to a more severe neurotoxicity in PC12 cells in response to Aβ1–40 . Furthermore, we corroborated that the active participation of AQP9 in AD progression is associated with Aβ-induced apoptosis both in vitro and in vivo . Taken together, our results reveal an important role of AQP9 in Aβ-induced pathogenesis of AD which deserves further investigation.